(untitled) (Advancements in Homeopathic Research, 2024)
Background: Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition with limited treatment options. This case series explores the potential of homeopathic Tarentula in managing ASD symptoms. Method: Two cases of moderate ASD (ISAA scores 132 and 151) were treated with Tarentula 200C for 1 year. Monthly follow-ups assessed progress using ISAA scores, caregiver reports, and clinical observations. Result: Both cases showed significant improvement. Case 1 (ISAA 132) achieved non-autistic status (ISAA 44) after 12 months. Case 2 (ISAA 151) achieved non-autistic status (ISAA 65) after 12 months. Caregivers reported satisfaction with the treatment. Conclusion: This case series suggests a potential role for Tarentula in improving ASD symptoms, particularly in moderate cases. However, further well-designed research is needed for stronger evidence. Key Words: Autism Spectrum Disorder, Homoeopathy, Tarentula,Indian Scale for Assessment of Autism